A Deep Study of Resistance Switching Phenomena in TaOx ReRAM Cells: System‐Theoretic Dynamic Route Map Analysis and Experimental Verification. (11th August 2022) - Ascoli, Alon; Menzel, Stephan; Rana, Vikas; Kempen, Tim; Messaris, Ioannis; Demirkol, Ahmet Samil; Schulten, Michael; Siemon, Anne; Tetzlaff, Ronald
Abstract: The multidisciplinary field of memristors calls for the necessity for theoretically‐inclined researchers and experimenters to join forces, merging complementary expertise and technical know‐how, to develop and implement rigorous and systematic techniques to design variability‐aware memristor‐based circuits and systems. The availability of a predictive physics‐based model for a memristor is a necessary requirement before commencing these investigations. An interesting dynamic phenomenon, occurring ubiquitously in non‐volatile memristors, is fading memory. The latter may be defined as the appearance of a unique steady‐state behavior, irrespective of the choice of the initial condition from an admissible range of values, for each stimulus from a certain family, for example, the DC or the purely‐AC periodic input class. This paper first provides experimental evidence for the emergence of fading memory effects in the response of a TaOx redox‐based random access memory cell to inputs from both of these classes. Leveraging the predictive capability of a physics‐based device model, called JART VCM v1, a thorough system‐theoretic analysis, revolving around the Dynamic Route Map graphic tool, is presented. This analysis allows to gain a better understanding of the mechanisms, underlying the emergence of history erase effects, and to identify the main factors, that modulate this nonlinear phenomenon, toward future potential applications. Abstract : This paper employs theoretic methods to gain a deep insight into the resistance switching phenomena emerging in a representative redox‐based random access memory cell. The application of a powerful analysis tool to an accurate physics‐based device model enables to understand the complex mechanisms, which induce memory loss in the non‐volatile memristor under both SET and RESET stimuli, opening up new interesting application scenarios.